Composite electron transport layer, preparation method thereof, perovskite solar cell and application
By using a composite electron transport layer of SnO2 layer with a thickness of ≥60nm and an IWO layer with a thickness of ≥5nm in perovskite solar cells, the problem of low opening voltage of perovskite solar cells is solved, and higher opening voltage and photoelectric conversion efficiency are achieved.
Patent Information
- Application Number
- CN202411760527.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
AI Technical Summary
In existing perovskite solar cells, the open voltage of the electron transport layer is relatively small, which affects the photoelectric conversion efficiency of the battery.
A composite electron transport layer is adopted, including C60 layer, SnO2 layer and IWO layer. The thickness of the SnO2 layer is ≥60nm and the thickness of the IWO layer is ≤5nm. The transmission rate and interface defects are increased through the thin IWO layer, and the electron transmission channel and light transmittance are increased.
It improves the opening voltage and stability of perovskite solar cells and enhances the photoelectric conversion efficiency.
Smart Images

Figure CN119653971A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a composite electron transport layer, a preparation method thereof, a perovskite solar cell and applications. Background Art
[0002] Perovskite solar cells have attracted widespread attention from academia and industry due to their many advantages, such as adjustable band gap and low cost. At present, the highest photoelectric conversion efficiency of single-junction perovskite solar cells has increased from 3.8% in 2009 to 26.25% in 2023. The rapid development of perovskite solar cells is based on the improvement of the quality of the perovskite material itself, and on the other hand, it also benefits from the development of efficient and stable interface transport layer preparation and its processing technology. However, the poor stability of perovskite itself and the interface transport layer has greatly hindered the commercialization process of perovskite solar cells. Therefore, the preparation of an efficient and stable interface transport layer is also an effective means to help improve the stability of perovskite solar cells.
[0003] In existing perovskite solar cells, metal oxide transport layer materials such as SnO2, TiO2, and NiO are widely used due to their low cost and stable performance. The electron transport layer (ETL) commonly used in large-scale inverted perovskite solar modules is C 60 For example, the existing patent CN116648076A discloses a perovskite solar cell, comprising a first electrode layer, a hole transport layer, a perovskite layer, an electron transport layer and a second electrode layer stacked in sequence, wherein the electron transport layer comprises C 60 layer and SnO2 layer, the C 60 The thicknesses of the SnO2 layer and the SnO2 layer are 10-30 nm and 15-25 nm, respectively.
[0004] However, when the electron transport layer of the above combination is applied to perovskite solar cells, the opening voltage is relatively low.
[0005] Therefore, how to solve the problem of low opening voltage of perovskite solar cells and improve the photoelectric conversion efficiency of the cells is a technical problem that needs to be solved urgently. Summary of the Invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a composite electron transport layer, a preparation method thereof, a perovskite solar cell and its application. By introducing a thin IWO layer, the present invention can improve the transmission rate of the composite electron transport layer, improve the interface defects between SnO2 and the electrode, and enable the battery to have a higher opening voltage and stability. In addition, the thick SnO2 layer can increase the electron transmission channel, so that the photogenerated electrons can be transmitted to the electrode more quickly and efficiently. The thin IWO layer can improve the light transmittance and increase the generation of photogenerated current. It can cooperate with the SnO2 layer to adjust the energy level matching between the perovskite layer and the electrode, promote charge transfer, and reduce charge recombination. The perovskite solar cell prepared based on this exhibits excellent photoelectric conversion efficiency. In order to achieve this purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a composite electron transport layer, wherein the composite electron transport layer comprises a stacked C 60 layer, SnO2 layer and IWO layer.
[0008] The thickness of the SnO2 layer is ≥60 nm, and the thickness of the IWO layer is ≤5 nm.
[0009] The present invention utilizes C 60 The combination of the SnO2 layer and the IWO layer is used as a composite electron transport layer. The introduction of the thin IWO layer can not only improve the transmission rate of the electron transport layer, but also help to improve the interface defects between SnO2 and the electrode. While ensuring the blocking effect of hole transmission and water and oxygen blocking, the battery can have a higher opening voltage and stability.
[0010] In the present invention, the thickness of the SnO2 layer is ≥60nm, for example, it can be 60nm, 70nm, 80nm, 90nm, 100nm or 120nm, and the thickness of the IWO layer is ≤5nm, for example, it can be 5nm, 4nm, 3nm, 2nm or 1nm.
[0011] The present invention limits the thickness of the SnO2 layer to ≥60nm and the thickness of the IWO layer to ≤5nm. A thicker SnO2 layer can significantly increase the electron transmission channel, provide more electron transmission paths, and enable photogenerated electrons to be transmitted to the electrode more quickly and efficiently. The thinner IWO layer not only further improves the light transmittance and increases the generation of photogenerated current, but also can cooperate with the thicker SnO2 layer to effectively adjust the energy level matching between the perovskite layer and the electrode, promote the transmission of charge, and reduce charge recombination losses. The perovskite solar cell prepared based on this has a high opening voltage while having a higher current, and exhibits excellent photoelectric conversion efficiency. If the thickness of the SnO2 layer is too small, it is not conducive to effectively blocking hole transmission; if the thickness of the IWO layer is too large, it is not conducive to electron transmission.
[0012] It should be noted that the IWO layer is a tungsten-doped indium oxide layer.
[0013] Preferably, the thickness ratio of the SnO2 layer to the IWO layer is (60-75):(1-5), wherein the selection range of the SnO2 layer "60-75" can be, for example, 60, 65, 70 or 75, and the selection range of the IWO layer "1-5" can be, for example, 1, 2, 3, 4 or 5.
[0014] In the present invention, the SnO2 layer and the IWO layer with a suitable thickness ratio help to improve the electron transmission performance, better match the energy level with the electrode, and increase the device turn-on voltage.
[0015] Preferably, the thickness of the SnO2 layer is 60-75 nm, for example, 60 nm, 65 nm, 70 nm or 75 nm.
[0016] Preferably, the thickness of the IWO layer is 1-5 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm or 5 nm.
[0017] Preferably, the C 60 The thickness of the layer is 15-25 nm, for example, 15 nm, 20 nm or 25 nm.
[0018] Preferably, the doping amount of tungsten in the IWO layer is 3-5 wt%, for example, 3 wt%, 4 wt% or 5 wt%.
[0019] In the present invention, doping the IWO layer with the aforementioned doping amount of tungsten helps to increase carrier concentration and mobility.
[0020] In a second aspect, the present invention provides a method for preparing the composite electron transport layer as described in the first aspect, the preparation method comprising the following steps:
[0021] C is deposited on the substrate in sequence 60 layer, a SnO2 layer and an IWO layer to obtain the composite electron transport layer.
[0022] The thickness of the SnO2 layer is ≥60 nm, and the thickness of the IWO layer is ≤5 nm.
[0023] Preferably, the C 60 Methods for depositing the layers include thermal evaporation or chemical vapor deposition.
[0024] Preferably, the SnO2 layer is deposited by any one of atomic layer deposition, solution deposition, thermal evaporation, template deposition or sol-gel deposition, or a combination of at least two thereof.
[0025] Preferably, the SnO2 layer is along the path away from the C 60The direction of the layers includes a first SnO2 layer and a second SnO2 layer stacked together, the first SnO2 layer is a loose and porous SnO2 film, and the second SnO2 layer is a dense SnO2 film; the preparation method of the loose and porous SnO2 film includes a template method or a sol-gel method, and the preparation method of the dense SnO2 film includes a solution method or a thermal evaporation method.
[0026] Preferably, the deposition method of the IWO layer includes a plasma coating method.
[0027] In a third aspect, the present invention provides a perovskite solar cell, comprising a stacked conductive substrate, a hole transport layer, a perovskite absorption layer, a composite electron transport layer as described in the first aspect, and an electrode.
[0028] Preferably, the hole transport layer comprises a nickel oxide layer and / or a copper oxide layer.
[0029] Preferably, the thickness of the hole transport layer is 5-20 nm, for example, 5 nm, 10 nm, 15 nm or 20 nm.
[0030] Preferably, the thickness of the composite electron transport layer is 76-105 nm, for example, 76 nm, 80 nm, 90 nm or 100 nm.
[0031] Preferably, the conductive substrate is transparent conductive glass, for example, ITO (indium tin oxide) conductive glass or FTO (fluorine-doped tin oxide) conductive glass.
[0032] Preferably, the general chemical formula of the perovskite absorption layer is ABX3, wherein A includes any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B includes lead ions and / or tin ions, and X is a halogen ion.
[0033] Preferably, the thickness of the perovskite absorption layer is 350-450 nm, for example, 350 nm, 360 nm, 380 nm, 420 nm or 450 nm.
[0034] Preferably, the electrode is a metal electrode, for example, a Cu electrode, an Ag electrode or an Au electrode.
[0035] In a fourth aspect, the present invention provides a photovoltaic module, comprising the composite electron transport layer as described in the first aspect, or the perovskite solar cell as described in the third aspect.
[0036] The numerical range described in the present invention includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention utilizes C 60 The combination of a SnO2 layer, a SnO2 layer, and an IWO layer serves as a composite electron transport layer. The introduction of a thin IWO layer not only improves the electron transport layer transmission rate, but also helps improve the interface defects between SnO2 and the electrode. While ensuring the hole transport blocking effect and the water and oxygen blocking effect, the battery has a higher opening voltage and stability. In addition, the thickness of the SnO2 layer is limited to ≥60nm and the thickness of the IWO layer is limited to ≤5nm. A thicker SnO2 layer can significantly increase the electron transport channel, provide more electron transport paths, and enable photogenerated electrons to be transmitted to the electrode more quickly and efficiently. The thinner IWO layer not only further improves the light transmittance and increases the generation of photogenerated current, but also works in conjunction with the thicker SnO2 layer to effectively adjust the energy level matching between the perovskite layer and the electrode, promote charge transport, and reduce charge recombination losses.
[0039] (2) The perovskite solar cell prepared based on the composite electron transport layer provided by the present invention has a high voltage at a high current and exhibits excellent photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the structure of the perovskite solar cell prepared in Example 1 of the present invention.
[0041] Among them, 1-FTO conductive glass; 2-hole transport layer; 3-perovskite absorption layer; 4-composite electron transport layer; 41-C 60 layer; 42-SnO2 layer; 43-IWO layer; 5-metal electrode. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0043] Example 1
[0044] This embodiment provides a composite electron transport layer, wherein the composite electron transport layer includes a stacked C 60 layer, SnO2 layer and IWO layer.
[0045] The thickness of the SnO2 layer is 60 nm, the thickness of the IWO layer is 3 nm, and the thickness ratio of the SnO2 layer to the IWO layer is 20:1; the C 60 The thickness of the layer is 20 nm; the doping amount of tungsten in the IWO layer is 3 wt %.
[0046] This embodiment also provides a method for preparing the composite electron transport layer as described above, the method comprising the following steps:
[0047] (1) A layer of C with a thickness of 20 nm was deposited on the substrate by thermal evaporation. 60 layer;
[0048] Among them, C 60 The evaporation rate of the layer is
[0049] (2) Using atomic layer deposition, C 60 A SnO2 layer with a thickness of 60 nm is deposited on the layer;
[0050] (3) A 5 nm thick IWO layer was deposited on the SnO2 layer using a plasma coating method.
[0051] This embodiment also provides a perovskite solar cell. The structural diagram of the perovskite solar cell is shown in FIG. Figure 1 As shown, the perovskite solar cell includes a stacked FTO conductive glass 1, a hole transport layer 2, a perovskite absorption layer 3, the composite electron transport layer 4 as described above, and a metal electrode 5.
[0052] The hole transport layer 2 is a nickel oxide layer with a thickness of 15nm; the perovskite absorption layer 3 is 400nm thick and has a chemical formula of MAPbI3; the composite electron transport layer 4 includes a stacked C 60 The total thickness of the SnO2 layer 41, the SnO2 layer 42 and the IWO layer 43 is 83 nm; the metal electrode 5 is a copper electrode with a thickness of 100 nm.
[0053] Example 2
[0054] This embodiment provides a composite electron transport layer, wherein the composite electron transport layer includes a stacked C 60 layer, SnO2 layer and IWO layer.
[0055] The thickness of the SnO2 layer is 80 nm, the thickness of the IWO layer is 4 nm, and the thickness ratio of the SnO2 layer to the IWO layer is 20:1; the C 60 The thickness of the layer is 20 nm; the doping amount of tungsten in the IWO layer is 3 wt %.
[0056] This embodiment also provides a method for preparing the composite electron transport layer as described above, the method comprising the following steps:
[0057] (1) A layer of C with a thickness of 20 nm was deposited on the substrate by thermal evaporation. 60 layer;
[0058] The evaporation rate is
[0059] (2) Using atomic layer deposition, C 60 A SnO2 layer with a thickness of 80 nm is deposited on the layer;
[0060] (3) A 4 nm thick IWO layer was deposited on the SnO2 layer using a plasma coating method.
[0061] This embodiment also provides a perovskite solar cell, which includes a stacked FTO conductive glass, a hole transport layer, a perovskite absorption layer, the composite electron transport layer as described above, and a metal electrode.
[0062] The hole transport layer is a nickel oxide layer with a thickness of 15 nm; the perovskite absorption layer has a thickness of 400 nm and a chemical formula of MAPbI3; the composite electron transport layer has a thickness of 104 nm; and the metal electrode is a copper electrode with a thickness of 100 nm.
[0063] Example 3
[0064] This embodiment provides a composite electron transport layer, wherein the composite electron transport layer includes a stacked C 60 layer, SnO2 layer and IWO layer.
[0065] The thickness of the SnO2 layer is 60 nm, the thickness of the IWO layer is 5 nm, and the thickness ratio of the SnO2 layer to the IWO layer is 12:1; the C 60 The thickness of the layer is 20 nm; the doping amount of tungsten in the IWO layer is 3 wt %.
[0066] This embodiment also provides a method for preparing the composite electron transport layer as described above, the method comprising the following steps:
[0067] (1) A layer of C with a thickness of 20 nm was deposited on the substrate by thermal evaporation. 60 layer;
[0068] The evaporation rate is
[0069] (2) Using atomic layer deposition, C 60 A SnO2 layer with a thickness of 60 nm is deposited on the layer;
[0070] (3) Using plasma coating method, a 5nm thick IWO layer is deposited on the SnO2 layer.
[0071] This embodiment also provides a perovskite solar cell, which includes a stacked FTO conductive glass, a hole transport layer, a perovskite absorption layer, the composite electron transport layer as described above, and a metal electrode.
[0072] The hole transport layer is a nickel oxide layer with a thickness of 15 nm; the perovskite absorption layer has a thickness of 400 nm and a chemical formula of MAPbI3; the composite electron transport layer has a thickness of 85 nm; and the metal electrode is a copper electrode with a thickness of 100 nm.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is that the thickness of the SnO2 layer is 70 nm.
[0075] The rest of the preparation methods and parameters remained the same as in Example 1.
[0076] Example 5
[0077] The difference between this embodiment and embodiment 1 is that the thickness of the SnO2 layer is 80 nm.
[0078] The rest of the preparation methods and parameters remained the same as in Example 1.
[0079] Example 6
[0080] The difference between this embodiment and embodiment 1 is that the thickness of the SnO 2 layer is adjusted to 10 nm, and the thickness of the IWO layer is adjusted to 100 nm, so that the thickness ratio of the SnO 2 layer to the IWO layer is 1:10.
[0081] The rest of the preparation methods and parameters remained the same as in Example 1.
[0082] Example 7
[0083] The difference between this embodiment and embodiment 1 is that the thickness of the SnO 2 layer is adjusted to 300 nm and the thickness of the IWO layer is adjusted to 3 nm, so that the thickness ratio of the SnO 2 layer to the IWO layer is 100:1.
[0084] The rest of the preparation methods and parameters remained the same as in Example 1.
[0085] Example 8
[0086] The difference between this embodiment and embodiment 1 is that the doping amount of tungsten in the IWO layer is 1 wt %.
[0087] The rest of the preparation methods and parameters remained the same as in Example 1.
[0088] Example 9
[0089] The difference between this embodiment and embodiment 1 is that the doping amount of tungsten in the IWO layer is 10 wt %.
[0090] The rest of the preparation methods and parameters remained the same as in Example 1.
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 1 is that no SnO2 layer is provided.
[0093] The rest of the preparation methods and parameters remained the same as in Example 1.
[0094] Comparative Example 2
[0095] The difference between this comparative example and Example 1 is that no IWO layer is provided.
[0096] The rest of the preparation methods and parameters remained the same as in Example 1.
[0097] Comparative Example 3
[0098] The difference between this comparative example and Example 1 is that the thickness of the SnO2 layer is 50 nm.
[0099] The rest of the preparation methods and parameters remained the same as in Example 1.
[0100] Comparative Example 4
[0101] The difference between this comparative example and Example 1 is that the thickness of the IWO layer is 6 nm.
[0102] The rest of the preparation methods and parameters remained the same as in Example 1.
[0103] Performance Testing
[0104] Five perovskite solar cells provided in the above examples and comparative examples were taken for photoelectric performance testing, and the average value was recorded.
[0105] Test conditions: test area 7200cm 2 , AM1.5, 1000W / m 2 , 25±2℃.
[0106] The test results are shown in Table 1.
[0107] Table 1
[0108]
[0109]
[0110] analyze:
[0111] As can be seen from the above table, the present invention utilizes C 60 Layer, SnO2 layer and IWO layer are combined as a composite electron transport layer. The introduction of a thin IWO layer can not only increase the transmission rate of the electron transport layer, but also help to improve the interface defects between SnO2 and the electrode. It can ensure the blocking effect of hole transmission and the water and oxygen blocking effect while making the battery have a higher opening voltage and stability. In addition, the thickness of the SnO2 layer is limited to ≥60nm, and the thickness of the IWO layer is ≤5nm. The thicker SnO2 layer can significantly increase the electron transmission channel, provide more electron transmission paths, and enable photogenerated electrons to be transmitted to the electrode more quickly and efficiently. The thinner IWO layer not only further improves the light transmittance and increases the generation of photogenerated current, but also can cooperate with the thicker SnO2 layer to effectively adjust the energy level matching between the perovskite layer and the electrode, promote the transmission of charge, and reduce charge recombination loss. The perovskite solar cell prepared based on the composite electron transport layer provided by the present invention has a higher opening voltage and exhibits excellent photoelectric conversion efficiency when having a higher current.
[0112] It can be seen from Example 1 and Examples 6-7 that if the thickness ratio of the SnO2 layer to the IWO layer is too small, the current loss is too large; if the thickness ratio of the SnO2 layer to the IWO layer is too large, the opening voltage increase is too small.
[0113] It can be seen from Example 1 and Examples 8-9 that if the tungsten doping amount in the IWO layer is too small or too large, the performance of the battery will be greatly reduced.
[0114] It can be seen from Example 1 and Comparative Example 1 that if the SnO2 layer is not provided, it will be detrimental to the transport of carriers, and at the same time, defects between interfaces will increase, resulting in a decrease in current and filling.
[0115] It can be seen from Example 1 and Comparative Example 2 that if the IWO layer is not provided, it is not conducive to adjusting the energy level matching between interfaces, resulting in the inability to increase the opening voltage.
[0116] It can be seen from Example 1 and Comparative Example 3 that if the thickness of the SnO2 layer is too small, the filling will be reduced.
[0117] It can be seen from Example 1 and Comparative Example 4 that if the thickness of the IWO layer is too large, both the filling and the current will decrease.
[0118] The applicant states that while the above-described embodiments illustrate the process of the present invention, the present invention is not limited to the above-described process steps, nor does it imply that the present invention must rely on the above-described process steps for implementation. Those skilled in the art will appreciate that any improvements to the present invention, equivalent substitutions for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.
Claims
1. A composite electron transport layer, characterized in that: The composite electron transport layer includes a stacked arrangement of C 60 layer, SnO2 layer and IWO layer; The thickness of the SnO2 layer is ≥60nm, and the thickness of the IWO layer is ≤5nm.
2. The composite electron transport layer according to claim 1, characterized in that: The thickness of the SnO2 layer is 60-75nm; Preferably, the thickness of the IWO layer is 1-5 nm.
3. The composite electron transport layer according to claim 1 or 2, characterized in that: The thickness ratio of the SnO2 layer to the IWO layer is (60-75):(1-5); Preferably, the C 60 The thickness of the layer is 15-25 nm.
4. The composite electron transport layer according to any one of claims 1 to 3, characterized in that: The doping amount of tungsten in the IWO layer is 3-5 wt %.
5. A method for preparing a composite electron transport layer according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: C is deposited on the substrate in sequence 60 layer, a SnO2 layer and an IWO layer to obtain the composite electron transport layer; The thickness of the SnO2 layer is ≥60nm, and the thickness of the IWO layer is ≤5nm.
6. The preparation method according to claim 5, characterized in that: The C 60 Layer deposition methods include thermal evaporation or chemical vapor deposition; Preferably, the SnO2 layer deposition method includes any one of atomic layer deposition, solution method, thermal evaporation method, template method or sol-gel method, or a combination of at least two thereof; Preferably, the deposition method of the IWO layer comprises a plasma coating method.
7. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a stacked conductive substrate, a hole transport layer, a perovskite absorption layer, a composite electron transport layer as claimed in any one of claims 1 to 4, and an electrode.
8. The perovskite solar cell according to claim 7, characterized in that: The hole transport layer includes a nickel oxide layer and / or a copper oxide layer; Preferably, the thickness of the hole transport layer is 5-20 nm; Preferably, the thickness of the composite electron transport layer is 81-100 nm.
9. The perovskite solar cell according to claim 7 or 8, characterized in that: The conductive substrate is transparent conductive glass; Preferably, the chemical formula of the perovskite absorption layer is ABX3, wherein A includes any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B includes lead ions and / or tin ions, and X is a halogen ion; Preferably, the thickness of the perovskite absorption layer is 350-450 nm; Preferably, the electrode is a metal electrode.
10. A photovoltaic module, characterized in that: The photovoltaic module comprises the composite electron transport layer as described in any one of claims 1 to 4, or comprises the perovskite solar cell as described in any one of claims 7 to 9.